Arrest of mouse preterm labor until term delivery by combination therapy with atosiban and mundulone, a natural product with tocolytic efficacy - Shajila Siricilla; Christopher J. Hansen; Jackson H. Rogers; Debasmita De; Carolyn L. Simpson; Alex G. Waterson; Gary A. Sulikowski; Stacey L. Crockett; Naoko Boatwright; Jeff Reese; Bibhash C. Paria; J. Newton; et al. (Elsevier, 2023)
There is a lack of FDA-approved tocolytics for the management of preterm labor (PL). In prior drug discovery efforts, we identified mundulone and mundulone acetate (MA) as inhibitors of in vitro intracellular Ca2+-regulated myometrial contractility. In this study, we probed the tocolytic potential of these compounds using human myometrial samples and a mouse model of preterm birth. In a phenotypic assay, mundulone displayed greater efficacy, while MA showed greater potency and uterine-selectivity in the inhibition of intracellular-Ca2+ mobilization. Cell viability assays revealed that MA was significantly less cytotoxic. Organ bath and vessel myography studies showed that only mundulone exerted inhibition of myometrial contractions and that neither compounds affected vasoreactivity of ductus arteriosus. A high-throughput combination screen identified that mundulone exhibits synergism with two clinical-tocolytics (atosiban and nifedipine), and MA displayed synergistic efficacy with nifedipine. Of these combinations, mundulone+atosiban demonstrated a significant improvement in the in vitro therapeutic index compared to mundulone alone. The ex vivo and in vivo synergism of mundulone+atosiban was substantiated, yielding greater tocolytic efficacy and potency on myometrial tissue and reduced preterm birth rates in a mouse model of PL compared to each single agent. Treatment with mundulone after mifepristone administration dose-dependently delayed the timing of delivery. Importantly, mundulone+atosiban permitted long-term management of PL, allowing 71% dams to deliver viable pups at term (>day 19, 4-5 days post-mifepristone exposure) without visible maternal and fetal consequences. Collectively, these studies provide a strong foundation for the development of mundulone as a single or combination tocolytic for management of PL.